Formulasi Strategi Layanan Asuransi Pertanian Menghadapi Perubahan Iklim - Irlha, Ika Maya; Suryanto, Suryanto (ENVIRO: Journal of Tropical Environmental Research, 2022)
Climate change is a global issues including in Indonesia. The agricultural sector is the most potential suffered by climate change. This research wants to identify the determinants that influence the supply of agricultural insurance products. The focus of this research complements the analysis of the insurance market, especially from the supply side. A quantitative method was choosen to analyze the primary data. We obtained the data by interviews with respondents who understand the problems of the insurance market. After the data collected and verified, we analysed the data using Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE), as well as SWOT analysis and QSPM analysis. The results show that insurance companies must have excellence in mastering information technology, qualified human resources, and always willing to adapt to new challenges.